Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In the face of so many daunting near-term challenges, U.S. government and industry are letting the crucial strategic issues of U.S. competitiveness slip below the surface. Five years ago, the National Academies prepared Rising Above the Gathering Storm, a book that cautioned: \

Legal Handbook for the New Starts Process - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s Transit Cooperative Research Program (TCRP) Legal Research Digest 30: Legal Handbook for the New Starts Process explores legal issues associated with the U.S. Federal Transit Administration2019s New Starts process.

Conducting Biosocial Surveys: Collecting, Storing, Accessing, and Protecting Biospecimens and Biodata - National Research Council (The National Academies Press, 2010)
Recent years have seen a growing tendency for social scientists to collect biological specimens such as blood, urine, and saliva as part of large-scale household surveys. By combining biological and social data, scientists are opening up new fields of inquiry and are able for the first time to address many new questions and connections. But including biospecimens in social surveys also adds a great deal of complexity and cost to the investigator's task. Along with the usual concerns about informed consent, privacy issues, and the best ways to collect, store, and share data, researchers now face a variety of issues that are much less familiar or that appear in a new light. In particular, collecting and storing human biological materials for use in social science research raises additional legal, ethical, and social issues, as well as practical issues related to the storage, retrieval, and sharing of data. For example, acquiring biological data and linking them to social science databases requires a more complex informed consent process, the development of a biorepository, the establishment of data sharing policies, and the creation of a process for deciding how the data are going to be shared and used for secondary analysis–all of which add cost to a survey and require additional time and attention from the investigators. These issues also are likely to be unfamiliar to social scientists who have not worked with biological specimens in the past. Adding to the attraction of collecting biospecimens but also to the complexity of sharing and protecting the data is the fact that this is an era of incredibly rapid gains in our understanding of complex biological and physiological phenomena. Thus the tradeoffs between the risks and opportunities of expanding access to research data are constantly changing. Conducting Biosocial Surveys offers findings and recommendations concerning the best approaches to the collection, storage, use, and sharing of biospecimens gathered in social science surveys and the digital representations of biological data derived therefrom. It is aimed at researchers interested in carrying out such surveys, their institutions, and their funding agencies.

Waste Forms Technology and Performance: Interim Report - National Research Council (The National Academies Press, 2010)
The Waste Forms Technology and Performance study examines requirements for waste form technology and performance in the context of the disposal system in which the waste will be emplaced. The Department of Energy, Office of Environmental Management requested this interim report to provide timely information for fiscal year 2011 technology development planning. The authoring committee has focused this interim report on opportunities associated with selected aspects of three components of its statement of task. These tasks are: The state-of-the-art tests and models of waste forms used to predict their performance for time periods appropriate to their disposal system. Potential modifications of waste form production methods that may lead to more efficient production of waste forms that meet their performance requirements. Potential new waste forms that may offer enhanced performance or lead to more efficient production. The committee judges that the opportunities identified in this report are sufficiently mature to justify consideration by DOE-EM as it plans its fiscal year 2011 technology development program.

Final Report of the National Academies' Human Embryonic Stem Cell Research Advisory Committee and 2010 Amendments to the National Academies' Guidelines for Human Embryonic Stem Cell Research - Institute of Medicine; National Research Council (The National Academies Press, 2010)
In 2005, the National Academies released the book, Guidelines for Human Embryonic Stem Cell Research, which offered a common set of ethical standards for a field that, due to the absence of comprehensive federal funding, was lacking national standards for research. In order to keep the Guidelines up to date, given the rapid pace of scientific and policy developments in the field of stem cell research, the Human Embryonic Stem Cell Research Advisory Committee was established in 2006 with support from The Ellison Medical Foundation, The Greenwall Foundation, and the Howard Hughes Medical Institute. As it did in 2007 and 2008, the Committee identified issues that warranted revision, and this book addresses those issues in a third and final set of amendments. Specifically, this book sets out an updated version of the National Academies' Guidelines, one that takes into account the new, expanded role of the NIH in overseeing hES cell research. It also identifies those avenues of continuing National Academies' involvement deemed most valuable by the research community and other significant stakeholders.

Review of the Proposal for the Gulf Long-Term Follow-Up Study: Highlights from the September 2010 Workshop: Workshop Report - Institute of Medicine (The National Academies Press, 2010)
The Gulf of Mexico oil spill is unprecedented not only in its size but also in the use of chemical dispersants and controlled burns to remove the oil. The National Institute of Environmental Health Sciences (NIEHS) is designing a study to investigate the health effects on clean-up workers. The IOM held a workshop to review and comment on NIEHS'o;s study protocol.

Examination of the U.S. Air Force's Science, Technology, Engineering, and Mathematics (STEM) Workforce Needs in the Future and Its Strategy to Meet Those Needs - National Research Council (The National Academies Press, 2010)
The Air Force requires technical skills and expertise across the entire range of activities and processes associated with the development, fielding, and employment of air, space, and cyber operational capabilities. The growing complexity of both traditional and emerging missions is placing new demands on education, training, career development, system acquisition, platform sustainment, and development of operational systems. While in the past the Air Force's technologically intensive mission has been highly attractive to individuals educated in science, technology, engineering, and mathematics (STEM) disciplines, force reductions, ongoing military operations, and budget pressures are creating new challenges for attracting and managing personnel with the needed technical skills. Assessments of recent development and acquisition process failures have identified a loss of technical competence within the Air Force (that is, in house or organic competence, as opposed to contractor support) as an underlying problem. These challenges come at a time of increased competition for technical graduates who are U.S. citizens, an aging industry and government workforce, and consolidations of the industrial base that supports military systems. In response to a request from the Deputy Assistant Secretary of the Air Force for Science, Technology, and Engineering, the National Research Council conducted five fact-finding meetings at which senior Air Force commanders in the science and engineering, acquisition, test, operations, and logistics domains provided assessments of the adequacy of the current workforce in terms of quality and quantity.

Guiding the Selection and Application of Wayside Energy Storage Technologies for Rail Transit and Electric Utilities - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s Transit Cooperative Research Program (TCRP) Web-Only Document 51: Guiding the Selection and Application of Wayside Energy Storage Technologies for Rail Transit and Electric Utilities is designed to help identify and implement effective wayside energy storage systems for rail transit. Energy storage applications addressed in the report include braking energy recapture, power quality voltage sag regulation, peak power reduction, and the development of energy storage substations.

Strategic Approach to the Evaluation of Programs Implemented Under the Tom Lantos and Henry J. Hyde U.S. Global Leadership Against HIV/AIDS, Tuberculosis, and Malaria Reauthorization Act of 2008 - Institute of Medicine; National Research Council (The National Academies Press, 2010)
At the request of Congress, the Institute of Medicine (IOM) will evaluate U.S. global programs to address HIV\/AIDS. This book outlines the IOM's strategic approach for this evaluation.

Review of the Department of Defense Enhanced Particulate Matter Surveillance Program Report - National Research Council (The National Academies Press, 2010)
Soldiers deployed during the 1991 Persian Gulf War were exposed to high concentrations of particulate matter (PM) and other airborne pollutants. Their exposures were largely the result of daily windblown dust, dust storms, and smoke from oil fires. On returning from deployment, many veterans complained of persistent respiratory symptoms. With the renewed activity in the Middle East over the last few years, deployed military personnel are again exposed to dust storms and daily windblown dust in addition to other types of PM, such as diesel exhaust and particles from open-pit burning. On the basis of the high concentrations observed and concerns about the potential health effects, DOD designed and implemented a study to characterize and quantify the PM in the ambient environment at 15 sites in the Middle East. The endeavor is known as the DOD Enhanced Particulate Matter Surveillance Program (EPMSP). The U.S. Army asked the National Research Council to review the EPMSP report. In response, the present evaluation considers the potential acute and chronic health implications on the basis of information presented in the report. It also considers epidemiologic and health-surveillance data collected by the USACHPPM, to assess potential health implications for deployed personnel, and recommends methods for reducing or characterizing health risks.

National Security Implications of Climate Change for U.S. Naval Forces: Letter Report - National Research Council (The National Academies Press, 2010)
The leaders of the U.S. Navy, Coast Guard, and Marine Corps have recognized the potential impact of climate change on naval forces' missions and have positioned their organizations to make adaptive changes. This report is the first component of a study to assess the implications of climate change for the U.S. Naval Services. Specifically, this report highlights issues that could have potential near-term impacts, impose a need for near-term awareness, or require near-term planning to ensure that longer-term naval capabilities are protected. The final report of this study will address all of the elements in the study's terms of reference and explore many potential implications of climate change not covered in this letter report.

The Role of Human Factors in Home Health Care: Workshop Summary - National Research Council (The National Academies Press, 2010)
The rapid growth of home health care has raised many unsolved issues and will have consequences that are far too broad for any one group to analyze in their entirety. Yet a major influence on the safety, quality, and effectiveness of home health care will be the set of issues encompassed by the field of human factors research2014the discipline of applying what is known about human capabilities and limitations to the design of products, processes, systems, and work environments. To address these challenges, the National Research Council began a multidisciplinary study to examine a diverse range of behavioral and human factors issues resulting from the increasing migration of medical devices, technologies, and care practices into the home. Its goal is to lay the groundwork for a thorough integration of human factors research with the design and implementation of home health care devices, technologies, and practices. On October 1 and 2, 2009, a group of human factors and other experts met to consider a diverse range of behavioral and human factors issues associated with the increasing migration of medical devices, technologies, and care practices into the home. This book is a summary of that workshop, representing the culmination of the first phase of the study.

Facilitating Climate Change Responses: A Report of Two Workshops on Knowledge from the Social and Behavioral Sciences - National Research Council (The National Academies Press, 2010)
The William and Flora Hewlett Foundation, understanding the need for policy makers at the national level to entrain the behavioral and social sciences in addressing the challenges of global climate change, called on the National Research Council to organize two workshops to showcase some of the decision-relevant contributions that these sciences have already made and can advance with future efforts. The workshops focused on two broad areas: (1) mitigation (behavioral elements of a strategy to reduce the net future human influence on climate) and (2) adaptation (behavioral and social determinants of societal capacity to minimize the damage from climate changes that are not avoided). Facilitating Climate Change Responses documents the information presented in the workshop presentations and discussions. This material illustrates some of the ways the behavioral and social sciences can contribute to the new era of climate research.

Improving State Voter Registration Databases: Final Report - National Research Council (The National Academies Press, 2010)
Improving State Voter Registration Databases outlines several actions that are needed to help make voter registration databases capable of sharing information within state agencies and across state lines. These include short-term changes to improve education, dissemination of information, and administrative processes, and long-term changes to make improvements in data collection and entry, matching procedures, and ensure privacy and security.

Review of the Department of Homeland Security's Approach to Risk Analysis - National Research Council
The events of September 11, 2001 changed perceptions, rearranged national priorities, and produced significant new government entities, including the U.S. Department of Homeland Security (DHS) created in 2003. While the principal mission of DHS is to lead efforts to secure the nation against those forces that wish to do harm, the department also has responsibilities in regard to preparation for and response to other hazards and disasters, such as floods, earthquakes, and other \

Preliminary Observations on Information Technology Needs and Priorities at the Centers for Medicare and Medicaid Services: An Interim Report - National Research Council (The National Academies Press, 2010)
Increasingly, the core mission of the Centers for Medicare and Medicaid Services (CMS), an agency of the Department of Health and Human Services, is expanding from one of focusing on prompt claims payment to one of becoming more broadly involved in improving health care quality and efficiency. The requirements for the information technology (IT) systems of CMS are changing as its mission changes, and the efforts to evolve its systems from those designed to support the agency's historical mission come in the midst of a push to modernize the nation's health care IT more broadly. These new challenges arise even as CMS must meet challenging day-to-day operational requirements and make frequent adjustments to its business processes, code, databases, and systems in response to changing statutory, regulatory, and policy requirements. In light of these and other emerging challenges, CMS asked the National Research Council to conduct a study that would lay out a forward-looking vision for the Centers for Medicare and Medicaid Services, taking account of CMS's mission, business processes, and information technology requirements. The study is being conducted in two phases. The first, resulting in the present volume, draws on a series of teleconferences, briefings, and an information-gathering workshop held in Washington, D.C., on September 27-28, 2010. The second phase, drawing on that workshop and on additional briefings, site visits, and committee deliberations, will result in a final report with recommendations, to be issued at the end of the project in 2011.

Forging the Future of Space Science: The Next 50 Years - National Research Council (The National Academies Press, 2010)
From September 2007 to June 2008 the Space Studies Board conducted an international public seminar series, with each monthly talk highlighting a different topic in space and Earth science. The principal lectures from the series are compiled in Forging the Future of Space Science. The topics of these events covered the full spectrum of space and Earth science research, from global climate change, to the cosmic origins of life, to the exploration of the Moon and Mars, to the scientific research required to support human spaceflight. The prevailing messages throughout the seminar series as demonstrated by the lectures in this book are how much we have accomplished over the past 50 years, how profound are our discoveries, how much contributions from the space program affect our daily lives, and yet how much remains to be done. The age of discovery in space and Earth science is just beginning. Opportunities abound that will forever alter our destiny.

Strategies for Improving the Project Agreement Process between Highway Agencies and Railroads - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s second Strategic Highway Research Program (SHRP 2) Report S2-R16-RR-1: Strategies for Improving the Project Agreement Process between Highway Agencies and Railroads examines the process by which highway agencies and railroads develop agreements for highway projects which interact with railways. The report examines the underlying causes of delay in the project-agreement process and developed model processes to address them.Appendix C of SHRP 2 Report S2-R16-RR-1 is available online in Microsoft Word format.An e-book version of this report is available for purchase at Google, Amazon, and iTunes.SHRP 2 Renewal Project R16 also developed two supplemental reports, one report about establishing a collaborative forum between transportation agencies and railroads and another report about the development of tools in this project.

Assessing the Effects of the Gulf of Mexico Oil Spill on Human Health: A Summary of the June 2010 Workshop - Institute of Medicine
From the origin of the leak, to the amount of oil released into the environment, to the spill's duration, the 2010 Gulf of Mexico oil spill poses unique challenges to human health. The risks associated with extensive, prolonged use of dispersants, with oil fumes, and with particulate matter from controlled burns are also uncertain. There have been concerns about the extent to which hazards, such as physical and chemical exposures and social and economic disruptions, will impact the overall health of people who live and work near the area of the oil spill. Although studies of previous oil spills provide some basis for identifying and mitigating the human health effects of these exposures, the existing data are insufficient to fully understand and predict the overall impact of hazards from the Deepwater Horizon oil spill on the health of workers, volunteers, residents, visitors, and special populations. Assessing the Effects of the Gulf of Mexico Oil Spill on Human Health identifies populations at increased risks for adverse health effects and explores effective communication strategies to convey health information to these at-risk populations. The book also discusses the need for appropriate surveillance systems to monitor the spill's potential short- and long-term health effects on affected communities and individuals. Assessing the Effects of the Gulf of Mexico Oil Spill on Human Health is a useful resource that can help policy makers, public health officials, academics, community advocates, scientists, and members of the public collaborate to create a monitoring and surveillance system that results in \

Report of a Workshop on the Scope and Nature of Computational Thinking - National Research Council (The National Academies Press, 2010)
Report of a Workshop on the Scope and Nature of Computational Thinking presents a number of perspectives on the definition and applicability of computational thinking. For example, one idea expressed during the workshop is that computational thinking is a fundamental analytical skill that everyone can use to help solve problems, design systems, and understand human behavior, making it useful in a number of fields. Supporters of this viewpoint believe that computational thinking is comparable to the linguistic, mathematical and logical reasoning taught to all children. Various efforts have been made to introduce K-12 students to the most basic and essential computational concepts and college curricula have tried to provide a basis for life-long learning of increasingly new and advanced computational concepts and technologies. At both ends of this spectrum, however, most efforts have not focused on fundamental concepts. The book discusses what some of those fundamental concepts might be. Report of a Workshop on the Scope and Nature of Computational Thinking explores the idea that as the use of computational devices is becoming increasingly widespread, computational thinking skills should be promulgated more broadly. The book is an excellent resource for professionals in a wide range of fields including educators and scientists.